2016
DOI: 10.7717/peerj.2155
|View full text |Cite
|
Sign up to set email alerts
|

Pteridine levels and head weights are correlated with age and colony task in the honey bee,Apis mellifera

Abstract: Background. The age of an insect strongly influences many aspects of behavior and reproduction. The interaction of age and behavior is epitomized in the temporal polyethism of honey bees in which young adult bees perform nurse and maintenance duties within the colony, while older bees forage for nectar and pollen. Task transition is dynamic and driven by colony needs. However, an abundance of precocious foragers or overage nurses may have detrimental effects on the colony. Additionally, honey bee age affects i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…We found that the markers vg and akhr , that typically exhibit significant changes during behavioral development [25, 26], are particularly suited for assessing bee biological age and, therefore, colony demographic changes. Markers that change with bee age but do not show consistent differences in expression between nurses and foragers may be better adapted to determining bee chronological age [20]. Since chronological and biological age are uncoupled in honey bees [42], identifying the chronological age of bees may not provide an accurate marker of colony state, at least during the foraging periods, when colony demographics often fluctuate according to changing environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the markers vg and akhr , that typically exhibit significant changes during behavioral development [25, 26], are particularly suited for assessing bee biological age and, therefore, colony demographic changes. Markers that change with bee age but do not show consistent differences in expression between nurses and foragers may be better adapted to determining bee chronological age [20]. Since chronological and biological age are uncoupled in honey bees [42], identifying the chronological age of bees may not provide an accurate marker of colony state, at least during the foraging periods, when colony demographics often fluctuate according to changing environment.…”
Section: Discussionmentioning
confidence: 99%
“…change in the nurse/forager ratio), and detecting such demographic changes could provide a new way to assess colony state in field-based studies. This redistribution or imbalance of the nurse/forager ratio could be revealed indirectly by the biological age of individuals [20]. Indeed, biological age, as opposed to chronological age, which is the time elapsed since the birth or emergence of the organism, refers to the changes in the physiological state of an organism that occur throughout its lifespan and is by definition dependent on external factors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] show a linear increase. In other insects such as the honey bee Apis mellifera [ 39 ] a correlation between ageing and pteridine level was also found, while, for example, the ants Polyrhachis sexspinosa [ 40 ] and Platythyrea punctata [ 41 ] showed no direct correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Another feature of pteridines is its potential relationship with behavioural aspects. For instance, pteridine levels in the honey bee may be related to age and colony task behaviour (Rinkevich et al, 2016). Dominance behaviour may also show a relationship with pterin-based visual signals in paper wasps (Izzo & Tibbetts, 2015).…”
Section: Discussionmentioning
confidence: 99%